Pancasila dan hak asasi manusia: Pilar etika dan keadilan dalam membangun masyarakat Indonesia - Qalbi, Nur Latifatul; Adhiyya, Sania Fawwaiza; Hafidh, Ena Nadhifah; Tajalla, Nurut (Maliki Interdisciplinary Journal, 2024)
This article discusses the importance of Pancasila as the basis of the Indonesian state and Human Rights (HAM) in building a just and civilized society based on the principles of ethics and justice using quantitative research methods. Pancasila is also a philosophy of life of the Indonesian nation that provides a moral and ethical foundation for the recognition and protection of Human Rights (HAM). By tracing the basic values of Pancasila such as the One Godhead, Fair and Civilized Humanity, Unity, People, and Social Justice. So that it can be known that these values are reflected in the principles and essence of human rights. In addition, this article also reviews the implementation and challenges in upholding human rights in Indonesia and strengthening human rights protection in the context of the cultural and social diversity of Indonesian society. Thus, this article contributes to understanding the complex relationship between Pancasila and human rights.